Use of pharyngeal packs in functional endoscopic sinus surgery: A randomized controlled trial. (26th August 2017) - Green, Ross; Konuthula, Neeraja; Sobrero, Maximiliano; Saini, Alok; Parasher, Arjun; Pool, Christopher; Levine, Adam I.; DeMaria, Samuel; Tufts, Ryan; Govindaraj, Satish; Iloreta, Alfred Marc
Abstract : Objective: To determine if pharyngeal packs have an effect on postoperative pain and postoperative nausea and vomiting in functional endoscopic sinus surgery (FESS). Study Design: Forty‐six patients scheduled for routine endoscopic sinus surgery were recruited into this study. The patients were randomly allocated to have or to not have pharyngeal packing prior to surgery. Methods: The placement of pharyngeal packs during FESS is controversial. Theoretically, pharyngeal packs may prevent postoperative nausea and vomiting by preventing ingestion of blood during sinus surgery. However, prior studies have not conclusively demonstrated this to be the case in FESS. Pharyngeal packs have been associated with complications including throat pain, aspiration, and death. The objective of this randomized control trial was to determine if pharyngeal packs have an effect on postoperative throat pain, nausea, and vomiting in order to determine their importance during FESS. Patients were blinded to intervention. Postoperatively, throat pain and nausea/vomiting scores were recorded. Results: There was no significant difference in mean throat pain at 4 hours following surgery ( P = 0.860). At 24 hours after surgery, patients without pharyngeal packing experienced more pain than those who had a throat pack placed ( P = 0.002). There was no significant difference in the level of nausea at 4 hours after surgery ( P = 0.315) or at 24 hours after surgery ( P = 0.315). Conclusion: We recommend against the routine use of placing pharyngeal packs during FESS. Level of Evidence: 1b. Laryngoscope, 127:2460–2465, 2017